Terapi Disabilitas Anak Berkebutuhan Khusus Pendidikan Anak Usia Dini dengan Eksperimen Berbasis Sains - Hena Dian Ayu; Henni Anggraini; Akhmad Jufriadi (Jurnal Pengabdian Masyarakat (ABDIRA), 2023)
This community service program aims to provide knowledge and prepare people with disabilities to have cognitive and social provisions and independence. The implementation method of this service program is by transferring technology and knowledge, through workshops, mentoring, monitoring and socializing books and demonstrating science experimental therapy. Monitoring and evaluation will also be carried out to find out the feedback and achievements of this activity. The method of this program is to use science experiment-based therapy with the concept of my environment is my experimental space.  The results of this program have proven to have an impact on improving the social and motor skills of partners. With experimentation, there will be social communication between the companion and the disability of ECE (Early Childhood Education)) crew so that the transfer of strengthening their social abilities and character can also be well established. Science experiments can be an easy, practical, precise and fun solution for them.